Cardiac muscle activation; the role of length dependent activation and the novel myosin activator danicamtiv. (25th November 2020) - Bell, K; Anto, A.R; Anderson, R.L; Del Rio, C.L; Henze, M
Abstract:  : B: Alterations in the length dependent activation (LDA) of left ventricular (LV) muscle fibres, the mechanistic driver of the Frank-Starling Law of the heart, are thought to mediate impaired LV function in heart failure (HF). However, little is known about LDA's role in the left atria (LA). Given the concomitant presence of LA dysfunction in HF, the purpose of this study was to compare/assess LDA on LA and LV muscle, as well to evaluate the effects of a novel small-molecule acto-myosin activator, danicamtiv (formerly known as MYK-491). M: LA and LV myofibrils from healthy Yucatan mini-pigs were used to determine biomechanical function with ATPase assays, with and without danicamtiv. Skinned LA and LV muscle fibres from these same animals were prepared to study contractile force, Ca2+ sensitivity, active/passive stiffness, and responsiveness to increasing sarcomere length (2.0 and 2.3). These parameters were also evaluated in the presence of danicamtiv. R: LA myofibrils had significantly faster ATPase and Pi release rates compared to LV, consistent with their respective alpha/beta myosin-isoform content. Despite increased metabolic rate, LA fibres generated less maximum isometric tension (12.3±1.96 vs 35.2±3.07 mN/mm 2 ) and had a lower pCa50 than LV fibres (5.66±0.02 vs 5.82±0.02), demonstrating reduced force-generating capability and Ca2+ sensitivity. Stretch of LV fibres resulted in a gain in tension over a range of pCas (pCa6.4, 6.2, 6.0, and 5.8, all p<0.05). However, in LA, LDA-induced gain was not significant at submaximal pCas (pCa6.4, 6.2, 6.0, all p>0.05). Stretch had no effect on active stiffness, but increased passive stiffness in both muscle types. Stretched LA fibres showed grater passive stiffness compared to LV (196.7±21.5 vs. 138.5±22.3 kN/m 3 ). A stiffer myofilament would in part explain the blunted ability of the LA to generate force in response to stretch. Danicamtiv activated both LA and LV myofibrils, increasing ATPase and Pi release rates, and increased Ca2+ sensitivity in fibres (ΔpCa; LV, 0.320±0.032; LA, 0.149±0.028, p<0.01). Unlike with stretch, danicamtiv had no effect on passive stiffness, yet altered the active stiffness/tension (S/T) relationship in both fiber types, but, differentially. In LV, danicamtiv increased the number of available heads (Y0; 129.9±26.3 vs 10.1±4.2 kN/m 3, p<0.001) with no significant effect on slope. In the LA, Y0 was largely unchanged with a significant increase in the slope of the S/T relationship (slope: 34.0±2.9 vs. 20.0±1.9 au, p<0.01). Together, these data suggest an increased number of force producing cross-bridges, without altering passive stiffness. C: These data confirm the functional differences between LA and LV muscle fibres and demonstrate a blunted ability of LA tissue to recruit force when stretched. The acto-myosin activator danicamtiv increased biochemical activity, Ca2+ sensitivity, and the active S/T relationship in LA and LV fibres without altering passive strain. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): MyoKardia Inc.